Postoperative Critical Care for Cardiac Surgical Patients - Dabbagh, Ali; Esmailian, Fardad; Aranki, Sary F. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Cardiac surgical procedures are among the most common and most complicated forms of surgery worldwide and the postoperative period is characterized by complex challenges. Among the factors determining ultimate clinical outcome, postoperative critical care is of major importance. This book adopts a clinical approach in explaining and analyzing the course of clinical care in patients undergoing cardiac surgery. Since the postoperative clinical status is directly influenced by preoperative and intraoperative factors, the early chapters briefly examine preoperative issues and the intraoperative course of cardiac surgery, with particular attention to anesthesia and the process of cardiopulmonary bypass. Subsequent chapters primarily address the critical care of patients by means of an organ-oriented approach, which will enable the reader to use the text as a "cookbook" of cardiac intensive care. This book is intended for use in daily practice by cardiac surgeons, cardiac anesthesiologists, intensivists and cardiac intensive care nurses.